Structural, Morphological, and LPG Sensing Properties of Al-Doped ZnO Thin Film Prepared by SILAR - Shampa Mondal; Shatabda Bhattacharya; P. Mitra (Advances in Materials Science and Engineering)
Undoped and aluminum doped zinc oxide (AZO) thin films were deposited on glass substrates by successive ion layer adsorption and reaction (SILAR) technique from ammonium zincate complex. The thin films are characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) for their structural and morphological studies. Both undoped and Al-doped film show strong preferred c-axis orientation. The texture coefficient (TC) of the film along (002) direction increases due to Al incorporation. SEM micrograph shows round shaped particles for pure ZnO. However AZO films show particles with off spherical shape and compact interconnected grains. Sensitivity of the film in presence of 80% LEL (lower explosive limit) of LPG increases with temperature and is maximum at 325°C. Significantly high sensitivity of 87% with reasonably fast response was observed for 1% Al-doped ZnO (AZO) film in presence of 1.6 vol% LPG at 325°C.